Serum IgE Predicts Difference of Population and Allergens in Allergic Diseases: Data from Weifang City, China - Zhang Xu-De; Guo Bei-Bei; Wang Xi-Juan; Li Hai-Bo; Zhang Li-Li; Liu Feng-Xia (Mediators of Inflammation)
Background. Immunoglobulin E (IgE) is the most important promoter of allergic inflammation. However, there are few systematic studies on IgE in age range, genders, disease spectrum, and time regularity. Aim. To screen the common allergens, allergen spectrum, and IgE difference between type 2 inflammatory allergic diseases and other allergic diseases in Weifang, China. Methods. A retrospective study was performed by estimating patients’ clinical data suffering from allergic diseases (urticaria, pollinosis, allergic rhinitis, atopic dermatitis, and bronchial asthma) between May 2019 and April 2020 using an allergen detection kit of Macro-Union Pharmaceutical. Results. 732 of the 1367 patients showed different antigen positive, and the positive rate was 53.5%. The most common allergens were dust mites, mixed fungi, Artemisia pollen, cat/dog dander, and cockroaches. There were 27.0% (369/1367) of the patients with single positive allergen-specific IgE (sIgE), 26.5% (363/1367) with multiple-positive IgE. The total immunoglobulin E (tIgE) levels varied with gender, age, and type of disease. There was a difference in the distribution of allergens between children and adults. A positive correlation between the serum-specific IgE and the corresponding local inhaled allergen density was observed. Conclusions. In this study, we found that type 2 inflammatory allergic diseases have higher serum IgE and a higher probability of inhaled sIgE positive. According to age, gender, and condition, serological IgE detection of allergens provides new insight into the early diagnosis and prevention of allergic diseases.